Virtual human influencers in live streaming commerce on social media platforms: exploring parasocial interactions with consumers in China - Yao, Lu; Tugiman, Nursafwah; Salehhuddin Sharipudin, Mohamad-Noor (Taylor's University Lakeside Campus, 2024)
The research explores the expanding role of virtual human influencers (VHIs) in digital marketing via parasocial interactions (PSIs) in live streaming commerce, with a focus on Chinese consumers. Grounded in the theoretical framework of the parasocial interaction theory, this study examines how VHIs attract viewers, engage with the material, and influence purchase decisions. Our study comprised two phases. Firstly, we conducted an extensive search across different scholarly databases and digital libraries using the keywords VHIs, PSIs, and live streaming commerce, which produced 35 relevant studies with matching content to the context of the present research. Then, we conducted a focus group discussion. Thematic analysis involved familiarisation with the data, coding, and theme development, ensuring an in-depth understanding of the participants’ views. Important findings indicate that VHIs leverage advanced technologies such as NLP (natural language processing) and AI (artificial intelligence) to establish a sense of familiarity and connection with viewers via personalisation, and interactive narrative. These strategies play an important part in enhancing customers’ parasocial interactions, which increases their trust, loyalty, and purchasing habits. Our study highlights the need for technological innovation and cultural atonement in order to enhance the effectiveness of VHIs. Our findings would assist digital marketing, consumer behaviour, and technology-human interaction by offering insights into the intricacies of parasocial interactions in the digital age.